Challenges and Teaching Strategies in English Language Teaching for Young Learners: A Descriptive Qualitative Study - Febria Sakinah; Wapuja Jayati Gathy Nst; Meliana Okvianti; Silvi Ramadhani; Risma Nurhasanah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
English language learning for young learners has become increasingly important in the era of globalization, as early exposure to a foreign language can significantly improve children’s linguistic competence and cognitive development. However, teaching English to young learners requires appropriate strategies due to their developmental characteristics and learning needs. This study aims to explore the challenges and teaching strategies in English language learning for young learners using a descriptive qualitative approach through a literature review method. The data were collected from various relevant journal articles, books, and academic sources, and analyzed using content analysis techniques to ensure the validity and comprehensiveness of the findings. The results show that English teaching for young learners faces several challenges, such as limited instructional time, insufficient learning facilities, large class sizes, low student motivation, and limited teacher competence in designing age-appropriate learning activities. These challenges are closely related to the learners’ characteristics, such as short attention spans, high imagination, and active learning behavior. To address these challenges, various interactive teaching strategies are recommended, including game-based learning, digital storytelling, songs, stories, and physical activities. These strategies have been proven to increase students’ motivation, participation, and language proficiency. In conclusion, the integration of learner characteristics, teaching challenges, and appropriate instructional strategies is essential to create effective English language learning for young learners. Teachers are encouraged to continuously adapt and innovate their teaching approaches to meet the diverse needs of learners in different educational contexts.